PERLINDUNGAN HUKUM TAKSI ONLINE DI IBUKOTA JAKARTA BERDASARKAN PERATURAN MENTERI PERHUBUNGAN REPUBLIK INDONESIA - Muhammad, Rashda Bintang (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
Absence of requirement consideration and lacking implementation of guidelines with respect to online cabbies' privileges are the central matters of online cab drivers. This is the inspiration for the creator to investigate the arrangements of the Regulation of the Minister of Transport of the Republic of Indonesia No. 118 of 2018 on the execution of extraordinary vehicle for enlist. In view of the consequences of the creator's meeting, it tends to be seen that there are as yet many advantages that web-based cabbies have not gotten, for example, having a region that doesn't reach out past Jakarta city, prompting the thickness of cab drivers. For online cabbies in Jakarta city, the most reduced least rates are resistance with the guidelines and implementation organizations don't give checking hardware to keep up with the security of clients and drivers. In light of the exploration aftereffects of the creator, it is realized that there are as yet many arrangements in Regulation No. 118 2018 of the Minister of Transport of the Republic of Indonesia on the execution of unique sanction transport that poor person been carried out. . ed by the candidate, with the self-view of the candidate to uphold the driver's freedoms. online taxi to make future web-based cab drivers more secure and more fruitful.